Reading Islam in Western Media: Hermeneutic Perspectives and the Hybridity of Southeast Asian Muslim Cultures - Chamadi, Muhamad Riza; Kuntarto, Kuntarto; Baedowi, Muhamad; Safitri, Lis (Suhuf: International Journal of Islamic Studies, 2025)
This article examines how Islam is represented in Western media and how Southeast Asian Muslim communities interpret and respond to these representations. Using Hans-Georg Gadamer’s philosophical hermeneutics and Homi K. Bhabha’s theory of cultural hybridity, this study explores the intersection between Western media narratives about Islam and the regional cultural contexts of Muslims in Southeast Asia. Representations of Islam in Western media often contain orientalist bias and symbolic simplifications that shape the global public’s perception of Muslims. However, Muslims do not always accept these depictions unquestioningly. Traditionally, Muslims in Southeast Asia have negotiated meaning and constructed new identities that combine Islamic traditions with modern values. This study employs a qualitative–hermeneutic approach by analyzing Western digital media texts including online news outlets (BBC, CNN) and popular audiovisual platforms (Netflix, YouTube) alongside Muslim audience responses collected from social media platforms such as Twitter, Instagram, and TikTok. The findings demonstrate the formation of a dynamic hybrid identity resulting from the interaction between Western media portrayals and Southeast Asian Muslim socio-religious practices in the digital era. This raises epistemological challenges in understanding religious authority and symbolic meaning in online spaces. Therefore, a more critical and contextual approach is needed in rereading the representation of Islam within the global media landscape.